Sustainability of Agricultural Land Management in Critical Areas in Malang Regency, Indonesia - Zairina, Anisa; Soemarno; Rachmansyah, Arief; Yanuwiadi , Bagyo; Purwanti, Gettik Andri; Amin Setyo Leksono; Abdullah, Saiful Arif (Malaysian Journal of Science (MJS), 2025)
This study aims to analyze the status of sustainable management of agricultural land in Pujon and Ngantang, East Java. This research was conducted in Pujon and Ngantang Subdistricts, Malang Regency, East Java, Indonesia. Data was obtained from a social survey by distributing questionnaires to 125 respondents. Respondents were purposely selected from locations prone to landslides. Of the 125 questionnaires distributed, 101 contained valid data. Respondents in this study consisted of farmers, landowners, and communities around landslide-prone lands. Data were analyzed using multidimensional scaling analysis. The sustainability status of landslide-prone land management on the social dimension was 80-100%, indicating very sustainable, while the sustainability index for other dimensions was 50-70% (moderately sustainable). The sustainability index for the ecological and technological dimensions had an exact value of 63.44%, whereas the economic dimension had a value of 63.23%. Attributes of the ecological dimension that significantly affect the sustainability of this dimension were the level of pest attacks on agricultural land, the influence of vegetation, and the slope of the land; for the economic dimension, attributes include opportunities for other sources of income, the stability of crop prices, and the availability of places to sell produce, while the attributes of the technological dimension include knowledge of water management, agricultural land technology, and landslide determination.